Measurement of Return of Islamic Knowledge Mobility (IROKM) on Women Entrepreneurs who are members of Bueka Aisyiyah Pringsewu Regency - Kusnindar, Arum Arupi; Rosidah, Ainur; Hidayatullah, Kholid; Sari, Sekar Arum (JESI (Jurnal Ekonomi Syariah Indonesia), 2025)
Introduction/Main Objectives: Islamic Knowledge Mobility (IROKM) is a key driver of women entrepreneurs’ performance in BUEKA Aisyiyah, Pringsewu Regency. This study examines its role in promoting business sustainability and well-being within a Sharia-based business context. The main problem addressed is how IROKM influences the sustainability and performance of women-led business, and to what extent moderating factors such as risk tolerance and knowledge-sharing transparency strengthen this relationship. This paper uniquely combines quantitative PLS-SEM analysis with qualitative NVivo insights to examine IROKM’s role in business performance—an area that has received limited attention, particularly in the context of women entrepreneurs operating under Islamic business principles in Indonesia.Methodology: This study used a mixed-method approach with PLS-SEM to measure IROKM’s impact on business performance and NVivo to analyze entrepreneurs’ perceptions, based on surveys and interviews with BUEKA Aisyiyah women entrepreneurs in Pringsewu Regency.Finding/Results: Results show IROKM significantly boosts business performance (path coefficient = 0.958), especially in revenue, sustainability, and networks, with risk tolerance and knowledge-sharing enhancing the effect. Qualitative data confirm Islamic values foster customer trust and loyalty. Conclusion: IROKM significantly boosts women entrepreneurs’ performance in an Islamic economic context, calling for targeted training, stronger Aisyiyah support, and wider Sharia-compliant financing to advance sustainable Sharia-based business models in Indonesia.